The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.jafc.8b05632
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Obesity and Hyperlipidemia by Heptamethoxyflavone in High-fat Diet-induced Rats

Abstract: Polymethoxyflavones (PMFs) have been shown to prevent obesity, ameliorate type 2 diabetes, and regulate lipid metabolism in vitro and in vivo. However, little is known about the contribution of 3,5,6,7,8,3′,4′-heptamethoxyflavone (HMF) to prevent obesity and regulate lipid metabolism in vivo. We aimed to investigate the potential efficacy of HMF on preventing obesity and hyperlipidemia in rats fed a high-fat diet (HFD) and its underlying mechanisms. Male Sprague–Dawley rats were fed a normal diet or an HFD wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 49 publications
2
57
0
Order By: Relevance
“…Our study provides evidence suggesting that HMF attenuates hepatic damage and steatosis caused by HFDs, with concurrent reductions in oxidative stress. A recent transcriptome analysis demonstrated that HMF supplementation markedly down-regulated hepatic genes related to adipogenesis and inflammatory responses, while increasing fatty acid oxidation and energy expenditure (Feng et al, 2019), and we hypothesize that this can contribute to the observed effect of HMF on the steatosis mitigation. that biological actions of the PMFs are largely due to their various metabolites.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our study provides evidence suggesting that HMF attenuates hepatic damage and steatosis caused by HFDs, with concurrent reductions in oxidative stress. A recent transcriptome analysis demonstrated that HMF supplementation markedly down-regulated hepatic genes related to adipogenesis and inflammatory responses, while increasing fatty acid oxidation and energy expenditure (Feng et al, 2019), and we hypothesize that this can contribute to the observed effect of HMF on the steatosis mitigation. that biological actions of the PMFs are largely due to their various metabolites.…”
Section: Discussionmentioning
confidence: 63%
“…(Kim et al, 2012) TAN ingestion mediated activities of enzymes important for carbohydrate metabolism and reduced glycosylated hemoglobin in diabetic rats (Sundaram et al, 2014). HMF has been also reported to regulate body weight, lipid profiles, and blood serum lipid levels in rats continuously fed a high-fat diet (HFD; Feng et al, 2019). Nobiletin (3′,4′,5,6,7,8-hex amethoxyflavone), a structurally related polymethoxylated flavone (PMF), improves adiposity, dyslipidemia, hyperglycemia, and insulin resistance in obese mice and also regulates glucose transport in muscles and white adipose tissue (Lee et al, 2010(Lee et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various natural bioactive compounds considered safe and effective, such as curcumin, propyl gallate, and resveratrol, have been explored for the treatment of obesity (WHO 2018; Feng et al. 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Three of the 4 active compounds (IC 50 <5 μM); curcumin (IC 50 = 2.2 μM), α-mangostin (IC 50 = 1.2 μM), and nobiletin (IC 50 = 0.9 μM), are reported to have SIRT1-activating effects (7,17,28,29,41,43,55). Another compound, HMF showing IC 50 = 1.0 μM, is reported to ameliorate brain and bone injuries (30,31,35,36,45), and recently shown to possess anti-metabolic effects (16). However, HMF-induced SIRT1-related functions are yet to be reported.…”
Section: Methodsmentioning
confidence: 99%